A hydrophobic layer of amino acid enabling dendrite-free Zn anodes for aqueous zinc-ion batteries. Issue 34 (16th August 2022) - Wen, Qing; Fu, Hao; Wang, Zhen-yu; Huang, Ying-de; He, Zhen-jiang; Yan, Cheng; Mao, Jing; Dai, Kehua; Zhang, Xia-hui; Zheng, Jun-chao
Abstract : The zinc l -cysteine functional layer was constructed by in situ etching Zn anode in 1 M l -cysteine solution. This functional layer not only improves the hydrophobicity and corrosion resistance of zinc anode, but also guides uniform zinc deposition. Abstract : Aqueous rechargeable zinc ion batteries have attracted increased attention for large-scale energy storage owing to their cost-effectiveness, safety and high volumetric energy density. However, aqueous rechargeable zinc ion batteries still face several challenges such as uncontrolled growth of zinc dendrites and side reactions, which seriously hinder their practical applications. Herein, we propose a strategy of interfacial engineering to kill two birds with one stone by introducing a zinc l -cysteine functional layer (Cys–Zn) with a unique sulfhydryl group on the surface of the Zn anode. This Cys–Zn layer not only improves the hydrophobicity of the zinc anode at the solid–liquid interface and thus mitigates the corrosion of the zinc anode, but also guides uniform zinc deposition. Besides, the in situ etching of Zn foil using l -cysteine not only leads to preferential exposure of the (002)Zn plane that further helps guide uniform deposition of zinc, but also removes the native oxide layer on Zn foil, leading to increased electrochemical surface area and reduced interfacial resistance. The computational results indicate that the Cys–Zn layer is strongly adsorbed on Zn foil to mitigate the penetration of zinc dendrites, while having great corrosion resistance against aqueous electrolytes. As such, the Cys–Zn-coated zinc anode achieved a stable long-term cycling performance over 2000 h for 2 mA h cm −2 at 2 mA cm −2 in Zn symmetrical cells. Besides, the Cys–Zn-coated zinc anode showed enhanced rate and cycling performance in Zn||MnO2 full cells and Zn||Cu half-cells, when compared with the bare Zn anode. We anticipate that this study provides a new interface modification layer on the inhibition of zinc dendrites and side reactions.